Evaluating the future terrestrial ecosystem contributions to carbon neutrality in Qinghai-Tibet Plateau. (10th November 2022) - Liu, Mengxue; Dong, Xiaobin; Wang, Xue-Chao; Zhao, Bingyu; Fan, Weiguo; Wei, Hejie; Zhang, Peng; Liu, Ranran
Abstract: China has proposed to achieve the carbon neutrality target by 2060. It is important for China to clearly understand the carbon sink of ecosystems. Most current studies focus on accounting for the carbon sink or carbon emission in the past and ignore the contribution of ecosystems to carbon neutrality in the future. The work presented in this paper projects land use changes in 2030 and 2060 under the business as usual (BAS), rapid economic development (RED), and ecological land protection (ELP) scenarios based on Multiple Objective Programming and GeoSOS-FLUS and calculates the carbon budgets and contributions of ecosystems to carbon neutrality in Qinghai during 2000–2060. The key findings are that the contributions of the terrestrial ecosystem to carbon neutrality in Qinghai are 9.92% (BAS), 10.03% (ELP) and 7.56% (RED) in 2030, and 3.23% (BAS), 3.28% (ELP) and 2.91% (RED) in 2060. These results indicate that the Qinghai ecosystem has carbon sink potential and the reduction of carbon emissions by humans is the core challenge in achieving carbon neutrality. Therefore, some recommendations have been made: 1) optimizing the land use structure to enhance the ecosystem sink in Qinghai; 2) continuing to implement the policies of ecological protection in Qinghai; 3) reducing the anthropogenic carbon emissions is the key to achieving carbon neutrality in 2060. This study not only offers data support and related policy recommendations to realize carbon neutrality goals but also provides a feasible method for future ecosystem contribution assessments under the goal of carbon neutrality. Highlights: Current land use policies in Qinghai are partial to ecological land protection. Terrestrial ecosystem contributions to carbon neutrality are decreasing. Terrestrial ecosystem contributions are similar in 2060 under three scenarios. Carbon emission reduction of social system is key to achieving carbon neutrality.